Screening for atrial fibrillation to prevent stroke in elderly individuals with or without preexisting cardiovascular disease. (3rd October 2022) - Xing, L Y; Diederichsen, S Z; Hojberg, S; Krieger, D W; Graff, C; Olesen, M S; Brandes, A; Kober, L; Haugan, K J; Svendsen, J H
Abstract: Background: Previous research has showed that various cardiovascular diseases (CVD) are associated with increased risks of atrial fibrillation (AF) and stroke. However, data on the interaction between CVD and AF screening efficacy are lacking. Purpose: To evaluate the influence of preexisting CVD on the effects of AF screening with long-term continuous monitoring. Methods: The LOOP Study (Atrial Fibrillation detected by Continuous ECG Monitoring using Implantable Loop Recorder to prevent Stroke in High-risk Individuals) randomized AF-naïve individuals aged ≥70 years and with additional stroke risk factors to either long-term screening with implantable loop recorder (ILR) and subsequent anticoagulation initiation upon detection of AF episodes ≥6 minutes, or usual care (the control group). In the current study, all participants from the LOOP Study were divided into two risk groups according to the presence of CVD (defined as ischemic heart disease, heart failure, previous stroke, valvular heart disease, or peripheral artery disease). The relative risks of outcomes in groupwise comparisons, as indicated by hazard ratio (HR), were assessed in the cause-specific Cox proportional-hazards model with death as competing risk. Results: Of 6004 participants included, 1997 (33.3%) had ≥1 CVD at baseline. Compared with no CVD, the presence of CVD was associated with increased risks of AF diagnosis in the ILR group (adjusted HR 1.32 [1.09–1.59]) and of stroke or systemic arterial embolism in the entire study cohort (adjusted HR 1.34 [1.06–1.69]). For ILR screening versus usual care, there was no decrease in stroke or systemic arterial embolism among participants with preexisting CVD (adjusted HR 1.13 [0.76–1.68]), whereas a significant risk reduction was obtained by screening among those without CVD (adjusted HR 0.64 [0.44–0.93]). The interaction was significant (adjusted p-value for interaction 0.041). Conclusions: In an elderly, high-risk population, ILR screening did not prevent stroke significantly in individuals with preexisting CVD, but it was associated with an approximately 40% risk reduction among those without CVD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The LOOP Study was funded by Innovation Fund Denmark [grant number 12-1352259], The Research Foundation for the Capital Region of Denmark, The Danish Heart Foundation [grant number 11-04-R83-A3363-22625], Aalborg University Talent Management Program, Arvid Nilssons Fond, Skibsreder Per Henriksen, R og Hustrus Fond, the European Union's Horizon 2020 program [grant number 847770], Læge Sophus Carl Emil Friis og hustru Olga Doris Friis' Legat, and an unrestricted grant from Medtronic.